(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
Nanotechnology is the science that is used in different fields and different fields. And it has great value from the benefits that go into in the It benefits various technological and industrial sectors, including information technology, energy, medicine, and transportation environment and its safety from pollutants, food safety, and many other things, as well as working to adapt materials in Very small scales have properties of active substances, and from these properties they are more durable and intertwine. In this work, the environmental aspect was applied and used, and the developers saw a need to develop nanocomposites to remove dyes from aqueous solutions to reduce environmental and health damage. Therefore, methods of synthesis of nanomaterials were developed in many different ways and in an increasing state. And the possibility of manipulating the chemical and physical properties by changing the particle size and using it in many of the above-mentioned applications and one of these applications is adsorption as in this work. To work on the adsorption property, the RGO nanoparticles were synthesized by the hydrothermal method and doped with zinc oxide (ZnO) nanoparticles that were also synthesized by the hydrothermyl method to produce (ZnO / RGO) nanocomposites and their properties were studied. The samples were examined with multiple analytical techniques such as X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), and energy dispersive X-ray analysis (EDX) to study their structure, morphology and thermal stability. And the identification of the reaction mechanism and the efficiency of absorption of rhodamine dye on this nanocomposite. Depending on different absorption conditions such as effect of temperature, mass dose of materials used, contact time and pH